Analisis Faktor-Faktor Yang Memengaruhi Loyalitas Pelanggan Dalam Melakukan Transaksi Online Pada E-Commerce XYZ - Aldila Amalia Saufika; Ari Kusyanti; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
One of the advantages of the internet is the existence of online business. E-commerce XYZ is one of the new e-commerce in Indonesia. The challenge as a new entrant is to build costumer trust. Issues related to e-commerce make an online business need to determine the level of costumer trust and satisfaction so that customer as loyal. This study aims to determine the relationship between costumer trust, satisfaction, and loyalty. Data were collected using questionnaire and distributed online. From 120 usable data obtained, data were tested using regression linear analysiss. The findings of this study show that perceived reputation, user interface quality, information quality, perceived security, and perceived privacy are positively related to trust while perceived size has no effect on trust. Futhermore, costumer trust is positively related to satisfaction. The finding of this study also shows that customer loyalty is influenced by customer trust and satisfaction.